PENGARUH MODAL, TINGKAT PENDIDIKAN, DAN PEMANFAATAN E-COMMERCE TERHADAP PRODUKSI DAN OMZET PENJUALAN IKM DI DENPASAR - Putra, I Kadek Suardana Di; Aswitari, Luh Putu (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2020)
Industrial currently growing rapidly is food and beverage. Food and beverage industry in Denpasar City makes a major contribution to absorption of labor and there is a distribution economic activities. The purpose this study was to analyze 1) effect of capital, education level, and the use of e-commerce on the production of food and beverage IKM in Denpasar, 2) effect of capital, education level, utilization of e-commerce and production on the sales turnover of food and beverage, 3) influence of capital, education level, and the use of e-commerce on sales turnover through production at food and beverage. Samples taken was 86. Data collection methods used observation, structured interviews, and in-depth interviews with path analysis techniques. Results showed, capital and education level had significant positive effect on production. Capital and production have significant effect, but level of education doesn’t have significant effect on the sales turnover of food and beverage. production and sales turnover at food and beverage use e-commerce higher than don’t use e-commerce. Production mediates relationship between capital, education level and  e-commerce on sales turnover at food and beverage IKM in Denpasar City.   Keywords: capital, level of education, utilization of e-commerce, production, and sales turnover.